Chronic Low Back Pain, Risk Factors and Effects on Bone Mineral Density - Bedriye Mermerci Başkan,; Filiz Sivas,; Tuba Güler,; Kürşat Özoran, (Archives of Rheumatology, 2009)
Objective: The aims of this study were to investigate bone mineral density (BMD) measurements and the strength of abdominal and dorsal muscles in premenopausal women with chronic low back pain (CLBP) and to determine the risk factors that could affect these parameters. Material and Methods: Fifty premenopausal women with CLBP were included in the study and the control group consisted of 30 healthy women. Physical examination and routine blood and urinary analyses were performed. Medical history consisted of questions regarding age, height, weight, educational level, duration of back pain, occupation, daily sports activities, consumption of cigarettes, alcohol, and caffeine, and number of children. The severity of back pain was measured by the Istanbul Back Pain Disability Index (IBPDI) and psychological status was evaluated by the Beck Depression Inventory (BDI). Muscle strength was evaluated using manual technique. BMD measurements were taken at the right forearm, hip, and lumbar vertebral regions. Results: There was no significant difference between groups in BMD values at all measurement sites. Abdominal and dorsal muscle strength was significantly higher in the control group than in the study group. In patients with CLBP, there was a significant relation between the body mass index (BMI) and BMD values of the Ward's triangle, femur neck and total forearm regions. In the patient group, there was a significant relation between the number of children and the BMD values of the femur neck and all forearm regions. There were significantly negative correlations between abdominal muscle strength and BMD values of the hip and femur neck. Conclusion: A comparison of BMD measurements between the two groups showed no significant difference. The authors believe that with implementation of exercise programs aimed at CLBP, a life standard with higher gratification levels and additional recoveries in terms of BMD levels will be obtained. (Turk J Rheumatol 2009; 24: 172-7)